Personalized Environmental Control Systems (PECS): Systematic review of benefits for thermal comfort, air quality, health, and human performance - Dolaana Khovalyg; Mariya P. Bivolarova; Jun Shinoda; Douaa Al-Assaad; Marika Vellei; Karol Bandurski; Giorgia Chinazzo; Ongun B. Kazanci; Joyce Kim; Tobias Kramer; Aleksandra Lipczynska; Shichao Liu; et al. (Building and Environment, 2025)

Mechanistic insights into the adaptive evolvability of spore heat resistance in Bacillus cereus sensu lato - Sadhana Khanal; Tom Dongmin Kim; Katrien Begyn; Wouter Duverger; Gertjan Kramer; Stanley Brul; Andreja Rajkovic; Frank Devlieghere; Marc Heyndrickx; Joost Schymkowitz; Frederic Rousseau; Véronique Broussolle; et al. (International Journal of Food Microbiology, 2024)

Enhancing agency and empowerment in agricultural development projects: A synthesis of mixed methods impact evaluations from the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) - Agnes R. Quisumbing; Ruth Meinzen-Dick; Hazel J. Malapit; Greg Seymour; Jessica Heckert; Cheryl Doss; Nancy Johnson; Deborah Rubin; Giang Thai; Gayathri Ramani; Emily Myers; Agnes Quisumbing; et al. (Journal of Rural Studies, 2024)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Linking annual variations of roe deer bag records to large-scale winter conditions: spatio-temporal development in Europe between 1961 and 2013 - Robert Hagen; Marco Heurich; Ilse Storch; Marc Hanewinkel; Stephanie Kramer-Schadt (European Journal of Wildlife Research, 2017)

Controls on carbon storage and weathering in volcanic soils across a high‐elevation climate gradient on Mauna Kea, Hawaii - Marc G. Kramer; Oliver A. Chadwick (Ecology, 2016)
Volcanic ash soils retain the largest and most persistent soil carbon pools of any ecosystem. However, the mechanisms governing soil carbon accumulation and weathering during initial phases of ecosystem development are not well understood. We examined soil organic matter dynamics and soil development across a high‐altitude (3,560–3,030 m) 20‐kyr climate gradient on Mauna Kea in Hawaii. Four elevation sites were selected (~250–500 mm rainfall), which range from sparsely vegetated to sites that contain a mix of shrubs and grasses. At each site, two or three pits were dug and major diagnostic horizons down to bedrock (intact lava) were sampled. Soils were analyzed for particle size, organic C and N, soil pH , exchangeable cations, base saturation, NaF pH , phosphorous sorption, and major elements. Mass loss and pedogenic metal accumulation (hydroxlamine Fe, Al, and Si extractions) were used to measure extent of weathering, leaching, changes in soil mineralogy and carbon accumulation. Reactive‐phase ( SRO ) minerals show a general trend of increasing abundance with increasing rainfall. However carbon accumulation patterns across the climate gradient are largely decoupled from these trends. The results suggest that after 20 kyr, pedogenic processes have altered the nature and composition of the volcanic ash such that it is capable of retaining soil C even where organic acid influences from plant material and leaching from rainfall are severely limited. Carbon storage comparisons with lower‐elevation soils on Mauna Kea and other moist mesic (2,500 mm rainfall) sites on Hawaii suggest that these soils have reached only between 1% and 15% of their capacity to retain carbon. Our results suggest that, after 20 kyr in low rainfall and a cold climate, weathering was decoupled from soil carbon accumulation patterns and the associated influence of vegetation on soil development. Overall, we conclude that the rate of carbon supply to the subsoil (driven by coupling of rainfall above ground plant production) is a governing factor of forms and amount of soil organic matter accumulation, while soil mineralogy remained relatively uniform.

Surficial gains and subsoil losses of soil carbon and nitrogen during secondary forest development - Megan L. Mobley; Kate Lajtha; Marc G. Kramer; Allan R. Bacon; Paul R. Heine; Daniel Deb Richter (Global Change Biology, 2015)
Reforestation of formerly cultivated land is widely understood to accumulate above‐ and belowground detrital organic matter pools, including soil organic matter. However, during 40 years of study of reforestation in the subtropical southeastern USA , repeated observations of above‐ and belowground carbon documented that significant gains in soil organic matter ( SOM ) in surface soils (0–7.5 cm) were offset by significant SOM losses in subsoils (35–60 cm). Here, we extended the observation period in this long‐term experiment by an additional decade, and used soil fractionation and stable isotopes and radioisotopes to explore changes in soil organic carbon and soil nitrogen that accompanied nearly 50 years of loblolly pine secondary forest development. We observed that accumulations of mineral soil C and N from 0 to 7.5 cm were almost entirely due to accumulations of light‐fraction SOM . Meanwhile, losses of soil C and N from mineral soils at 35 to 60 cm were from SOM associated with silt and clay‐sized particles. Isotopic signatures showed relatively large accumulations of forest‐derived carbon in surface soils, and little to no accumulation of forest‐derived carbon in subsoils. We argue that the land use change from old field to secondary forest drove biogeochemical and hydrological changes throughout the soil profile that enhanced microbial activity and SOM decomposition in subsoils. However, when the pine stands aged and began to transition to mixed pines and hardwoods, demands on soil organic matter for nutrients to support aboveground growth eased due to pine mortality, and subsoil organic matter levels stabilized. This study emphasizes the importance of long‐term experiments and deep measurements when characterizing soil C and N responses to land use change and the remarkable paucity of such long‐term soil data deeper than 30 cm.

A meta-analysis of two genome-wide association studies to identify novel loci for maximum number of alcoholic drinks - Manav Kapoor; Jen-Chyong Wang; Leah Wetherill; Nhung Le; Sarah Bertelsen; Anthony L. Hinrichs; John Budde; Arpana Agrawal; Kathleen Bucholz; Danielle Dick; Oscar Harari; Victor Hesselbrock; et al. (Human Genetics, 2013)

Long‐term carbon storage through retention of dissolved aromatic acids by reactive particles in soil - Marc G. Kramer; Jonathan Sanderman; Oliver A. Chadwick; Jon Chorover; Peter M. Vitousek (Global Change Biology, 2012)
Soils retain large quantities of carbon, thereby slowing its return to the atmosphere. The mechanisms governing organic carbon sequestration in soil remain poorly understood, yet are integral to understanding soil‐climate feedbacks. We evaluated the biochemistry of dissolved and solid organic carbon in potential source and sink horizons across a chronosequence of volcanic soils in Hawai'i. The soils are derived from similar basaltic parent material on gently sloping volcanic shield surfaces, support the same vegetation assemblage, and yet exhibit strong shifts in soil mineralogy and soil carbon content as a function of volcanic substrate age. Solid‐state 13 carbon nuclear magnetic resonance spectra indicate that the most persistent mineral‐bound carbon is comprised of partially oxidized aromatic compounds with strong chemical resemblance to dissolved organic matter derived from plant litter. A molecular mixing model indicates that protein, lipid, carbohydrate, and char content decreased whereas oxidized lignin and carboxyl/carbonyl content increased with increasing short‐range order mineral content. When solutions rich in dissolved organic matter were passed through Bw‐horizon mineral cores, aromatic compounds were preferentially sorbed with the greatest retention occurring in horizons containing the greatest amount of short‐range ordered minerals. These minerals are reactive metastable nanocrystals that are most common in volcanic soils, but exist in smaller amounts in nearly all major soil classes. Our results indicate that long‐term carbon storage in short‐range ordered minerals occurs via chemical retention with dissolved aromatic acids derived from plant litter and carried along preferential flow‐paths to deeper B horizons.

Multiple-level defoliation assessment with hyperspectral data: integration of continuum-removed absorptions and red edges - Shaokui Ge; Raymond I. Carruthers; Marc Kramer; James H. Everitt; Gerald L. Anderson (International Journal of Remote Sensing, 2011)

Dynamics of photosynthetic photon flux density (PPFD) and estimates in coastal northern California - Shaokui Ge; Richard G. Smith; Constantinos P. Jacovides; Marc G. Kramer; Raymond I. Carruthers (Theoretical and Applied Climatology, 2011)

Old and stable soil organic matter is not necessarily chemically recalcitrant: implications for modeling concepts and temperature sensitivity - MARKUS KLEBER; PETER S. NICO; ALAIN PLANTE; TIMOTHY FILLEY; MARC KRAMER; CHRISTOPHER SWANSTON; PHILLIP SOLLINS (Global Change Biology, 2011)
Soil carbon turnover models generally divide soil carbon into pools with varying intrinsic decomposition rates. Although these decomposition rates are modified by factors such as temperature, texture, and moisture, they are rationalized by assuming chemical structure is a primary controller of decomposition. In the current work, we use near edge X‐ray absorption fine structure (NEXAFS) spectroscopy in combination with differential scanning calorimetry (DSC) and alkaline cupric oxide (CuO) oxidation to explore this assumption. Specifically, we examined material from the 2.3–2.6 kg L −1 density fraction of three soils of different type (Oxisol, Alfisol, Inceptisol). The density fraction with the youngest 14 C age (Oxisol, 107 years) showed the highest relative abundance of aromatic groups and the lowest O ‐alkyl C/aromatic C ratio as determined by NEXAFS. Conversely, the fraction with the oldest C (Inceptisol, 680 years) had the lowest relative abundance of aromatic groups and highest O ‐alkyl C/aromatic C ratio. This sample also had the highest proportion of thermally labile materials as measured by DSC, and the highest ratio of substituted fatty acids to lignin phenols as indicated by CuO oxidation. Therefore, the organic matter of the Inceptisol sample, with a 14 C age associated with ‘passive’ pools of carbon (680 years), had the largest proportion of easily metabolizable organic molecules with low thermodynamic stability, whereas the organic matter of the much younger Oxisol sample (107 years) had the highest proportion of supposedly stable organic structures considered more difficult to metabolize. Our results demonstrate that C age is not necessarily related to molecular structure or thermodynamic stability, and we suggest that soil carbon models would benefit from viewing turnover rate as codetermined by the interaction between substrates, microbial actors, and abiotic driving variables. Furthermore, assuming that old carbon is composed of complex or ‘recalcitrant’ compounds will erroneously attribute a greater temperature sensitivity to those materials than they may actually possess.

Meteoric diagenesis of Quaternary carbonate-rocky talus slope successions (Northern Calcareous Alps, Austria) - Diethard G. Sanders; Marc Ostermann; Jan Kramers (Facies, 2010)

Quaternary carbonate-rocky talus slope successions (Eastern Alps, Austria): sedimentary facies and facies architecture - Diethard Sanders; Marc Ostermann; Jan Kramers (Facies, 2009)

Aragonite and calcite cementation in “boulder-controlled” meteoric environments on the Fern Pass rockslide (Austria): implications for radiometric age dating of catastrophic mass movements - Marc Ostermann; Diethard Sanders; Christoph Prager; Jan Kramers (Facies, 2007)